Предмет: Алгебра,
автор: nastyateplova9
Упростите выражение х(х^2-3x)-(x-5)(x^2+5x+25) при х= 4
Ответы
Автор ответа:
2
x( x^2 - 3x ) = x^3 - 3x^2
2) - ( x - 5 )( x^2 + 5x + 25 ) = - ( x^3 - 125 ) = - x^3 + 125
3) x^3 - 3x^2 - x^3 + 125 = - 3x^2 + 125
при х = 4
- 3 * 16 + 125 = - 48 + 125 = 77
2) - ( x - 5 )( x^2 + 5x + 25 ) = - ( x^3 - 125 ) = - x^3 + 125
3) x^3 - 3x^2 - x^3 + 125 = - 3x^2 + 125
при х = 4
- 3 * 16 + 125 = - 48 + 125 = 77
Похожие вопросы
Предмет: География,
автор: margotsay09
Предмет: Литература,
автор: sofa8757
Предмет: Математика,
автор: zeninmaki11037
Предмет: Алгебра,
автор: Аноним
Предмет: Алгебра,
автор: ульяна4567889